Síndrome de imunodeficiência adquirida em idosos - Tibúrcio, Alberto Saraiva; Bazin, Anna Ricordi; Dalston, Marcos Olivier; Setúbal, Sérgio; Tavares, Walter (Brazilian Journal of Sexually Transmitted Diseases, 1994)
Acquired Immunodefficiency Syndrome strikes all socioeconomic and age strata, including people over 60 years of age. Despi te our small patient sample, we have found a greater difficulty in diagnosing people in this age group, expressed by longer evolutions until the making of appropriate diagnostic !'fOCedures. Patients were analysed regarding their risk factors and/or behavior, as well as clinicai manifestations. ln addition, some possible causes for the increasing incidence of AIDS in older people are suggested.